Hematological and biochemical changes in a cow with metastatic cholangiocarcinoma - Beserra, Lucas Alencar Fernandes; Afonso, José Augusto Bastos; Mendonça, Carla Lopes de; Zache, Eduardo; Silva, Thailan Arlindo da; Coutinho, Luiz Teles; Souza, Maria Isabel; Arenales, Alexandre (Brazilian Journal of Veterinary Pathology, 2022)
We describe here hematological and biochemical findings in a cow with metastatic cholangiocarcinoma. On physical examination, apathy with congested mucous membranes, tachycardia and enlarged abdomen; hypoperistalsis in rumen, abomasum and intestines. In hematological examination, icteric plasma with leukocytosis by neutrophilia with regenerative left shift and inversion of the proportion between lymphocytes and segmented neutrophils, and hypofibrinemia. In serum biochemistry: hyperproteinemia, hypoalbuminemia, hyperglobulinemia, low albumin/globulin ratio and high levels of aspartate aminotransferase, gamma-glutamyltransferase. The cow died and in necropsy was observed a severe and diffuse increase in volume predominantly on the hepatic right lobe and moderate increase of volume in mesenteric lymph nodes. Which was diagnosed microscopically as a cholangiocarcinoma, characterized by arrangements in irregular and coalescent ducts. In conclusion, cholangiocarcinoma may cause important hematological and biochemical changes in cattle.